Toxicity of magnesium alloy biodegradation products in experiment - Yu. M. Neryanov; M. L. Golovakha; I.F. Belуеnіchev; V.N. Chorny; E.V. Yatsun (Patologìâ)
The article presents information on the study of possible toxic effects of biodegradation products of original magnesium-based alloy on laboratory rats. The used laboratory methods of investigation are described. Author has examined biochemical parameters of plasma on the base of which endogenous intoxication in rats was studied. It was found out that products of alloy biological resorption don’t cause toxic effects on tissues and don’t enhance cell destruction, that is evidenced by the absence of signs of endogenous intoxication and oxidative damage of functional macromolecules.